Different dosage regimens of nifedipine, labetalol, and hydralazine for the treatment of severe hypertension during pregnancy: a network meta-analysis of randomized controlled trials - Hui-Zhen Wu; Yuan Cheng; Ding Yu; Ji-Bin Li; Yun-Fa Jiang; Zhong-Ning Zhu (Hypertension in Pregnancy, 2022)
Objectives This network meta-analysis aimed to compare the efficacy and safety of intravenous (IV) hydralazine, oral nifedipine, and IV labetalol with different dosage regimens in the treatment of severe hypertension during pregnancy. Methods A comprehensive literature search was performed on PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov for randomized controlled trials (RCTs) exploring the effects of hydralazine, nifedipine, and labetalol in the treatment of severe hypertension during pregnancy. Results A total of 21 RCTs with 2183 patients comparing 7 regimens (oral nifedipine 50,60,90 mg; hydralazine 15,25 mg; and labetalol 220,300 mg) were identified. Compared with IV labetalol 300 mg, nifedipine 50,60, and 90 mg significantly improved the successful treatment rate of severe hypertension during pregnancy, nifedipine 50 and 90 mg and IV hydralazine 25 mg required significantly fewer doses to achieve target blood pressure (BP), and nifedipine 50 mg took significantly shorter time to achieve target BP. Subgroup analysis showed that only nifedipine 50 mg tablets, not capsules, required a significantly shorter time and fewer doses to achieve target BP than IV labetalol 300 mg. Moreover, nifedipine 60,90 mg showed superior effectiveness than IV hydralazine 15,25 mg in the successful treatment rate of severe hypertension during pregnancy. SUCRA analysis suggested that nifedipine 50,60,90 mg as the better regimens with the lower rates of overall ADR and neonatal complications. Conclusion These findings demonstrated the superiority of oral nifedipine 50,60,90 mg, especially oral nifedipine 50 mg tablets, in the treatment of severe hypertension during pregnancy than IV labetalol 300 mg, while oral nifedipine 60,90 mg also showed superiority in the successful treatment rate of severe hypertension during pregnancy than IV hydralazine 15,25 mg. However, the limitations of the underlying data indicate that future large-scale and rigorous RCTs are needed to confirm such findings.